Kinerja Perusahaan Terkait dengan Terapan dan Kompetensi Teknologi Informasi - Eko Purwanto (Jurnal Siasat Bisnis, 2014)
Abstract Investment in information technology (IT) implementation in organizations tends to increase manufacturing in Indonesia. Various studies show that implementation of IT that is applied has a major impact on company performance. This study aims to answer, whether at manufacturing organizations in Indonesia, the implementation of IT is applied and competencies have an impact, both directly and indirectly to the performance. The sample of this study is a company registered in the Department of Industry and Trade in East Java, which apply information and communication technologies in local area network. There are 117 companies with 500 employees or more participated in this study. Data were analyzed using SEM, with the application of SPSS and AMOS. The results of this study indicate that the more complete implementation of information technology applied in the company, and the higher the competence of knowledge in information technology, the higher the company's organizational performance is achieved. Keywords: Implementation IT, Competence IT, Organization Performance.